Analgesic and Anti-inflammatory Activities of the Stem Bark of Yellow Flamboyant (Peltophorum pterocarpum) - O.K. Ogbeide; C.J. Ogbonnaya; E. Asakitikpi; D.O. Uyi; B.O. Aluge; O. Nosakhare; W.O. Otahagwa; C.A. Ehigie; U. Omoruyi; O.S. Aifuwa; B.O. Gabriel (Journal of Applied Sciences and Environmental Management, 2019)
Peltophorum pterocarpum (family; Fabaceae) is an evergreen perennial crop grown in tropical gardens. Different parts of this tree are being used for the management of many diseases. This study investigated the acute toxicity, analgesic and anti-inflammatory potentials of n-hexane extract of P. pterocarpum stem bark. Acute oral toxicity of n-hexane extract of P. pterocarpum stem bark was investigated using standard method. Analgesic activity was investigated by using acetic acid-induced writhing model, using indomethacin as a reference drug. Antiinflammatory activity of n-hexane extract of P. pterocarpum stem bark was investigated by using formalin-induced paw licking model, using aspirin as standard drug. In the acute toxicity study, mortality was observed at 500 and 2500 mg/kg body weight. In the acetic acid induced writhing test, the n-hexane extract of P. pterocarpum (100 and 200 mg/kg body weight) showed a significant reduction in the number of writhing with 55.5 % and 60 % of inhibition respectively. In formalin-induced rat paw oedema test for acute inflammation, the n-hexane extract of P. pterocarpum in 50, 100 and 200 mg/kg body weight showed 26.00 %, 27.89 % and 32.27 % inhibition of oedema respectively after 4hours, which is comparable to that of standard drug-aspirin (33.59 %). These results validated that the extract of P. pterocarpum possesses significant analgesic and anti-inflammatory properties.